Hope Springs : a proper romance - Eden, Sarah M. (Eden, Sarah M. Hope Springs series, 2014)
Irish-born Kate Macauley is caught in the feud that is raging between the American farmers and the Irish immigrants in the small Wyoming town of Hope Springs. She is also torn between loving two very different men.